Augmented‐reality‐based skills training for robot‐assisted urethrovesical anastomosis: a multi‐institutional randomised controlled trial. (16th August 2014) - Chowriappa, Ashirwad; Raza, Syed Johar; Fazili, Anees; Field, Erinn; Malito, Chelsea; Samarasekera, Dinesh; Shi, Yi; Ahmed, Kamran; Wilding, Gregory; Kaouk, Jihad; Eun, Daniel D.; Ghazi, Ahmed; et al.
<x xml:space="preserve">Abstract</x> Objective To validate robot‐assisted surgery skills acquisition using an augmented reality (AR)‐based module for urethrovesical anastomosis (UVA). Methods Participants at three institutions were randomised to a Hands‐on Surgical Training (HoST) technology group or a control group. The HoST group was given procedure‐based training for UVA within the haptic‐enabled AR‐based HoST environment. The control group did not receive any training. After completing the task, the control group was offered to cross over to the HoST group (cross‐over group). A questionnaire administered after HoST determined the feasibility and acceptability of the technology. Performance of UVA using an inanimate model on the daVinci Surgical System (Intuitive Surgical Inc., Sunnyvale, CA, USA) was assessed using a UVA evaluation score and a Global Evaluative Assessment of Robotic Skills (GEARS) score. Participants completed the National Aeronautics and Space Administration Task Load Index (NASA TLX) questionnaire for cognitive assessment, as outcome measures. A Wilcoxon rank‐sum test was used to compare outcomes among the groups (HoST group vs control group and control group vs cross‐over group). Results A total of 52 individuals participated in the study. UVA evaluation scores showed significant differences in needle driving (3.0 vs 2.3; P = 0.042), needle positioning (3.0 vs 2.4; P = 0.033) and suture placement (3.4 vs 2.6; P = 0.014) in the HoST vs the control group. The HoST group obtained significantly higher scores (14.4 vs 11.9; P 0.012) on the GEARS. The NASA TLX indicated lower temporal demand and effort in the HoST group (5.9 vs 9.3; P = 0.001 and 5.8 vs 11.9; P = 0.035, respectively). In all, 70% of participants found that HoST was similar to the real surgical procedure, and 75% believed that HoST could improve confidence for carrying out the real intervention. Conclusion Training in UVA in an AR environment improves technical skill acquisition with minimal cognitive demand.